Impact of a six-week training program on physical fitness and performance of young tennis players: a cluster analysis approach - João P. Oliveira; João P. Oliveira; João P. Oliveira; Daniel A. Marinho; Daniel A. Marinho; Tatiana Sampaio; Tatiana Sampaio; Tatiana Sampaio; Bulent Kilit; Jorge E. Morais; Jorge E. Morais (Frontiers in Sports and Active Living)
This study aimed to classify young tennis players into sub-groups (clusters) based on their performance and physical fitness determinants and to analyze their cluster assignment change over six weeks of intervention. A sample of young athletes aged 10–14 years was used, and players were classified according to their International Tennis Number (ITN) and various physical fitness metrics after a six-week specific training program. Clusters were also analyzed for cluster assignment changes across pre-test and post-test interventions. The results showed that the performance variables in all clusters improved at the end of the intervention. Specifically, ITN scores improved by an average of 15% (p < 0.05), the 5-m sprint times improved by 8.5% on average (p < 0.01), and the T-drill agility test showed a 10% reduction in completion time (p < 0.01). However, key determinants for cluster formation assessment scores differed, meaning that the training resulted in the physical fitness profiles changing over time. Improvement in 5-m sprint and T-drill agility tests showed that the current program was effective in improving movement characteristics that are vital to a tennis player. Movement between clusters was observed, with some players improving their classification while others regressed, highlighting the need for individualized training interventions to optimize player development. Individualized responses to training are common among young athletes, reflecting varying developmental stages. Clustering can help tailor training programs to the specific needs of different groups. In summary, this study highlights the effects of specific training on young tennis players and emphasizes the necessity of considering individual differences in growth and training responses.